Innovative answers to the food security question in Africa - International Livestock Research Institute (International Livestock Research Institute, 2012)
Honorable Bob McMullen, the Australian Parliamentary Secretary for International Development, Australia and a delegation from The Australian Agency for International Development (AusAID) visited the Biosciences eastern and central Africa-International Livestock Research Institute (BecA-ILRI) Hub on 3rd November 2009. During his visit, Hon. McMullen highlighted the opportunities presented by Australia's increased focus on Africa food security issues. Mr. McMullan also complimented the enthusiasm of the scientists at BecA-ILRI in finding homegrown solutions to African agricultural challenges.